FILSAFAT HUKUM SEBAGAI LANDASAN PERLINDUNGAN HAK ASASI MANUSIA - Reni Okpirianti; Nur Husni Emilson; Amelia Tri Rahayu; Fadiah Adilah Kusmayadi; Nesa Claudia Putri; Tri Daryanti; Resi (The Juris, 2026)
The relationship between legal philosophy and human rights is fundamentally rooted in fundamental questions regarding the source of legitimacy of legal norms. Legal philosophy, particularly natural law and legal positivism, plays a significant role in determining the concept of justice that underlies human rights protection. This paper employs normative legal research. The implementation of human rights values has not demonstrated sufficient consistency. The gap between norms and practice remains apparent, particularly in the resolution of cases of gross human rights violations that have yet to achieve legal clarity. Considering these challenges, this study recommends a reorientation of human rights policy through regulatory harmonization, revisions to rules that potentially limit civil liberties, and strengthening state accountability mechanisms in all cases of violation. These steps are expected to establish a system that not only recognizes human rights declaratively but also ensures the actual fulfillment of these rights in people's daily lives.